The Relationship Between Motivation And Nurse Compliance In The Use Of Personal Protective Equipment In The Internal Medicine Room Of Blambangan Hospital Banyuwangi - Diana Kusumawati; Sholihin; Rani Diana Balqis; Emy Indriyani (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction : Disease transmission can be at risk for all health workers if during the action the patient does not pay attention to preventive measures by using PPE. The application of the use of personal protective equipment that is not optimal can be caused by the low compliance factor of the nurse herself in doing it. The purpose of the study was to determine the relationship between motivation and nurse compliance in the use of personal protective equipment in the Internal Medicine Room of Blambangan Hospital Banyuwangi in 2024. Methods : The research design used is analytical by design cross sectional. The population in this study is all nurses in the Internal Medicine Room of Blambangan Hospital Banyuwangi 2024, as many as 34 people, with techniques total sampling. Research instruments using questionnaire sheets are then analyzed using tests rank spearman. Results of the study found that most of the 26 respondents (76.5%) in the high motivation category, and most of the 28 respondents (82.4%) in the compliant category used PPE. Calculation results by test rank spearman, obtained the value ρ = 0.000 < α 0.05, then Ho rejected means that there is The relationship between motivation and nurse compliance in the use of personal protective equipment in the Internal Medicine Room of Blambangan Hospital Banyuwangi in 2024. With high relationship closeness category (r = 0.835). Conclusion : Seeing the results of this study, nurses need to increase usage PPE in providing nursing care according to SOPs set by the hospital